2014
DOI: 10.1530/erc-14-0225
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals mutant genes with low penetrance involved in MEN2A-associated tumorigenesis

Abstract: Activating rearranged during transfection (RET) mutations function as the initiating causative mutation for multiple endocrine neoplasia type 2A (MEN2A). However, no conclusive findings regarding the non-RET genetic events have been reported. This is the first study, to our knowledge, examining genomic alterations in matched MEN2A-associated tumors. We performed exome sequencing and SNP array analysis of matched MEN2A tumors and germline DNA. Somatic alterations were validated in an independent set of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Examples of diseases for which exome sequencing has been used to detect a causative variant include Leber congenital amaurosis ( Wang et al 2011 ), Alzheimer disease ( Sassi et al 2014 ), maturity-onset diabetes of the young ( Johansson et al 2012 ), high myopia ( Shi et al 2011 ), autosomal recessive polycystic kidney disease ( Xu et al 2014 ), amyotrophic lateral sclerosis ( Johnson et al 2010 ), immunodeficiency leading to infection with human herpes virus 8 causing Kaposi Sarcoma ( Byun et al 2010 ), acromelic frontonasal dystois ( Smith et al 2014 ), and a number of cancer predisposition mutations ( e.g. , Yan et al 2011 ; Greif et al 2012 ; Snape et al 2012 ; Kiiski et al 2014 ; Cai et al 2015 ).…”
Section: Uses In Humansmentioning
confidence: 99%
“…Examples of diseases for which exome sequencing has been used to detect a causative variant include Leber congenital amaurosis ( Wang et al 2011 ), Alzheimer disease ( Sassi et al 2014 ), maturity-onset diabetes of the young ( Johansson et al 2012 ), high myopia ( Shi et al 2011 ), autosomal recessive polycystic kidney disease ( Xu et al 2014 ), amyotrophic lateral sclerosis ( Johnson et al 2010 ), immunodeficiency leading to infection with human herpes virus 8 causing Kaposi Sarcoma ( Byun et al 2010 ), acromelic frontonasal dystois ( Smith et al 2014 ), and a number of cancer predisposition mutations ( e.g. , Yan et al 2011 ; Greif et al 2012 ; Snape et al 2012 ; Kiiski et al 2014 ; Cai et al 2015 ).…”
Section: Uses In Humansmentioning
confidence: 99%
“…MTC from MEN2 patients rarely show any other somatic driver mutations (103). Investigating the genomic landscape of sporadic MTCs revealed mutually exclusive oncogenic mutations in RET and RAS subtypes K and H in 75 and 15% respectively (104,105,106).…”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%
“…[148] Exome sequencing of MTCs associated with MEN2A also identified the expected RET mutations, but also suggested that low frequency mutations such as those found in EIF4G1 may also play a role in MEN2Aassociated tumorigenesis by indirectly altering the RET pathway. [158] A similar study was undertaken by Smith et al [159] in MTCs lacking an identifiable RET mutation. Interestingly, this group found a recurrent mutation in the ESR2 gene which encodes the estrogen receptor beta (ER).…”
Section: Nets -Thyroidmentioning
confidence: 84%